Programmable Logic Controller Analog Input Learning Module: An Expert-Based Evaluation - Wati, Miladiah Setio; Maryadi, Totok Heru Tri; Badarudin, Rohjai; Al Hakim, Vando Gusti (PTE FTK UIN Ar-Raniry, 2025)
This study aims to validate the analog input learning module of programmable logic controller (PLC). This module was developed using the OMRON CP1H PLC type which has analog input and analog output configurations. Scientific studies on the quality standards of learning modules are the basis for the development of this instrument. The content validity test was carried out by evaluation experts, while media and material experts evaluated the printed media and PLC material aspects. The results of the study showed an assessment of the media side with an average score of the format aspect of 14.5, the organizational aspect of 27.5, the shape and size of the letters of 13.0, and the consistency aspect of 29.5 which was categorized as